membaca Metode Guru dalam Mengenalkan Membaca Awal Anak Usia Dini di Tk Kemala Bhayangkari 1 Padang - Irval Noviardi; Asdi Wirman (Universitas Islam Lamongan, 2025)
Early childhood education encompasses the nurturing of young minds through stimulating experiences that foster various dimensions of a child's growth and potential, preparing them for the subsequent stage of their educational journey. An essential area for development is the enhancement of children's language abilities, particularly their reading skills. This includes recognising letters, understanding letter shapes, discerning letter sounds, and comprehending how these sounds combine to form words. This study seeks to elucidate the implementation of early reading initiatives for young learners at the Kemala Bhayngkari 1 Padang Kindergarten. The research methodology employed is descriptive in nature, utilising a qualitative framework. The approach to data collection employs techniques such as observation, interviews, and documentation. The methodologies employed in the analysis encompass data reduction, data presentation, and the formulation of conclusions. The technique employed to ensure data validity is known as data triangulation. The outcomes of the preliminary reading introduction activities for children at Kemala Bhayangkari 1 Padang Kindergarten align seamlessly with the meticulously crafted plans that were established beforehand. The process of introducing children to reading involves the careful design of a module each week, aligned with the curriculum's topics and sub-topics, which is subsequently distilled into a comprehensive learning plan. The introduction of early reading activities for children is executed through a diverse array of approaches, including singing, play, demonstration, storytelling, conversation, questioning, and assignments. This is complemented by the use of letter cards, storybooks, and visual aids. The assessment of children's early reading engagement is conducted through a variety of evaluative methods aligned with the curriculum, including checklists, photo series, annotated notes, and samples of children's work.